Pulmonary Oxygen Toxicity: Investigation and Mentoring - Hedley-Whyte, John (The Ulster Medical Society, 2008)
SUMMARY: At sea level oxygen is toxic to man when breathed for more than twenty-four hours at a percentage greater than about forty percent. Pulmonary pathology is the first manifestation in subjects with previously normal lungs. In patients with pre-existing lung disease the results are often additive. There is, however, great variation in response from subject to subject and between patients. Queen's Belfast and Harvard University Medical School have been the sites of seminal investigations. Mentoring at both universities is due to training at the University of Copenhagen.